When people do not 'Zol': Reduced emergency centre attendance of patients with chronic obstructive pulmonary disease during coronavirus disease 2019 lockdown with the accompanying tobacco sales ban in South Africa - Piero Saieva; Louis S. Jenkins (AOSIS, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has spread throughout the world, with devastating effects of the virus as well as the repercussions of the resulting 'lockdowns'. South Africa went into a national lockdown in March 2020 to mitigate the impact of the virus. This included a ban on the sales of tobacco and electronic cigarette products. The ban has been a highly contentious issue in South Africa, discussed worldwide, which has drawn many criticisms. The prevalence rate of smoking in South Africa was around 21.5%, with the Western Cape province having a prevalence rate of 39%. We compared the number of chronic obstructive pulmonary disease (COPD) presentations at a large regional referral hospital in the Western Cape province from January to August 2019 with the same period in 2020. Electronic emergency centre data showed a reduction of 69.28% in COPD presentations. To control for some confounders for the same period, we also reviewed patients presenting with urinary tract infections, which showed only a 30.60% reduction. This notable reduction in COPD presentations reduced service pressure of emergency centre and most likely benefitted patients' health. Further research and policies are needed to ensure ongoing reduction in the prevalence of smoking.